Effect of loan value and collateral on value of mortgage default - Itoo, R. A. (2016)
This study explore the factors influencing mortgage loan default by using the data of mortgage default case from Jammu and Kashmir Bank. To achieve the study objectives sixteen variables are taken. The variables are categorized into three dimensions as borrower’s profile, loan value contents and collateral security. The tools used for analysis of data describing mortgage loan defaulter’s are chi-square, regression, ANOVA, and logistic regression through SPSS 18.0. The results indicate that the borrower’s gender, borrower’s age, borrower’s marital status, the borrower’s income, loan rate, loan type, loan amount, amount repaid, LTV, LTI, form of collateral security, Value of collateral security, purpose of loan and secondary finance on collateral security are significantly positively correlated with the defaulter’s outstanding loan amount. While as education qualification of borrower is significantly negatively correlated with defaulter’s outstanding loan amount. Logistic regression results indicate that income, secondary finance on collateral security and interest rate are mainly responsible for mortgage default.